Education Paradigm Reconstruction: Efforts to Increase Synergy between Teachers and Supervisors in Increasing Academic Supervision - Yanti Budayasti (Global Writing Academica Researching and Publishing, 2022)
The purpose of this study was to analyze efforts to increase the synergy between teachers and supervisors in improving academic supervision. This research uses qualitative research with a case study approach. The types of data in this study are primary data and secondary data. This research was conducted using a best practice approach carried out in the Mande sub-district, with the object of research including nine fostered teachers from Middle School 1 Mande, Middle School 2 Mande, Middle School 3 Mande, Middle School Plus Al-Bidayah Islamic Middle School Ibnu Umar , all of which are located in Cianjur district. Based on the results of the data and analysis, it can be concluded that to achieve the learning goals that have been determined, both teachers and supervisors must be able to work together and synergize well. Because with good synergy between teachers and supervisors, both parties can continue to upgrade their skills and professionalism, as well as make the learning process more focused and measurable in accordance with the provisions set out in the national education system.